A Review of HVDC Circuit Breaker (International Journal of Engineering and Computer Science, 2018)
The increasing interest in development, operation and integration of large amount of renewable energy resources like offshore wind farms and photovoltaic generation in deserts leads to an emerging demand on development of multi-terminal high voltage direct current (MTDC) systems. Due to preformed studies, voltage source converter based HVDC (VSC-HVDC) system is the best option for realising future multi-terminal HVDC system to integrate bulk amount of energy over long distances to the AC grid. The most important drawback of VSC -HVDC systems is their need for fast HVDC circuit breakers. This paper aims at summarizing HVDC circuit breakers technologies including recent significant attempts in development of modern HVDC circuit breaker. A brief functional analysis of each technology is presented. Additionally, different technologies based on derived information from literatures are compared. Finally, recommendations for improvement of circuit breakers are presented.